Analisis Tindak Kecurangan Dalam Sistem PPDB SMA Di Kota Depok Tahun 2024 Terhadap Implementasi E-Government - Tias Rahma Dewi; Alifah Jasmine Kallista Remanu; Revalyza Misbah; Najwa Adhwa Ramadhani; Fatkhuri, Fatkhuri (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
This research aims to analyze the fraud that occurs in the high school PPDB system in Depok City in 2024 towards the implementation of e-government. This research also analyzes more deeply the factors and impacts that occur due to fraud in the high school PPDB in Depok City. The research method used is a qualitative approach with a descriptive research type. Sources of data obtained through primary data, which comes from direct interviews with one of the high schools in Depok City, and secondary data derived from various literature on high school PPDB. The result of this research is that there are still irresponsible people behind the PPDB Online system in Depok City. The data obtained from the field also states that the irresponsible person comes from someone who has a strong relationship. Strong bureaucratic reforms are needed from both the government and the community to be able to minimize and prevent the occurrence of high school PPDB fraud in Depok City from happening again. The contribution of this research to the development of political science is to broaden the understanding of the implementation of e-government in the education aspect, namely how the dynamics between government-owned technology and the implementation of local bureaucratic practices. In this case, online PPDB is designed to increase transparency and accountability, but instead opens new loopholes for various indications of fraud that have the potential to weaken the effectiveness of the system. This research shows that digital innovation in public policy must be accompanied by structural reform in order to democratize public services effectively.